Palliative radiotherapy for multiple liver metastases: a retrospective analysis of 73 cases. (9th April 2022) - Ito, Kei; Ogoshi, Yumi; Shimizuguchi, Takuya
Abstract: Background: Whole-liver radiotherapy for diffuse liver metastases can improve symptoms and abnormal liver-related blood data. However, whole-liver radiotherapy is uncommonly used in clinical practice in Japan. Therefore, we aimed to clarify palliative radiotherapy outcomes in Japanese patients with liver metastases. Methods: We retrospectively reviewed databases in our institution to identify patients treated with radiotherapy (8 Gy in a single fraction) for multiple liver metastases between December 2014 and April 2021. The endpoints included pain response, liver-related blood data and adverse effects. We investigated aspartate transaminase, alanine transaminase, lactate dehydrogenase, alkaline phosphatase, γ-glutamyl transpeptidase and albumin. The mean values at whole-liver radiotherapy and after 2–4 weeks were compared using the Wilcoxon rank-sum test. Results: A total of 73 cases in 71 patients were included. The median clinical target volume was 2118 ml (range, 133–7867 ml). Fifty-seven patients (78%) had finished aggressive treatment at the time of radiotherapy. The median follow-up period was 6 weeks. The pain response rate was 64% (18/28). The mean values of five parameters significantly improved 2–4 weeks after radiotherapy compared to those at baseline: aspartate transaminase (118 vs. 83 U/l P < 0.01); alanine transaminase (84 vs. 61 U/l P < 0.01); lactate dehydrogenase (1351 vs. 1007 U/l P = 0.027); alkaline phosphatase (1624 vs. 1216 U/l P < 0.01) and γ-glutamyl transpeptidase (663 vs. 450 U/l P = 0.037). No patients experienced radiation-induced liver disease. Conclusions: Palliative radiotherapy is efficient and safe in Japanese patients with liver metastases. These findings will help encourage whole-liver radiotherapy use in Japan. Abstract : Palliative radiotherapy achieved good pain palliation and significant improvement of hepatic blood data for Japanese patients with LM. Moreover, no patients experienced radiation-induced liver disease.